Characterization Of DAC - Korakkottil Kunhi Mohd, Shukri (Universiti Sains Malaysia, 2006)
This dissertation presents about characterization of Digital-to-Analog Converter (DAC). It is included a theory, problem facing, problem solving, characterization techniques, results and lastly conclusion. DAC chip used here for characterization process was ICM7363 Quad 12 bit from IC Microsystems (ICmic). ICM7363 is a serial digital input type of DAC. In order for the DAC to work properly, serial data input, clock signal, chip select signal and clear signal are needed. 8051 microcontroller board was built for data generation and as well as all the signal needed in order to activate the DAC. In this project 8051 microcontroller circuit were combined with DAC circuit and a set of switches. There are 17 switches available. One of these switches used as a test functionality switch. Function of this switch is to indicate whether the DAC is working or not. Other 16 switches used as data input of DAC. 8051 microcontroller was programmed to read the condition of all those switches and then generate signals to the DAC. DAC is then producing an analog output that is proportional with digital input value. The program was written in assembly language. This program was then compiled and burnt into ROM. Program start running whenever supply is connected. The output produced by the DAC is then can be measured and characterized. Measuring tool used here is digital mutimeter. From the output, DAC parameters such as resolution, accuracy, offset error, full-scale error, differential non-linearity, integral non-linearity, full scale range, settling time, maximum conversion rate and signal-to-noise ratio can be characterize. Resolution of the DAC is shown by plotting a histogram of the output. Typical output value for adjacent input is 0.01V. This is the DAC resolution. DNL and INL of DAC are shown by plotting a graph of the output. From here, ideal value and measured value can be compared. DNL and INL are approximately 1LSB for intermediate voltage that is around 2V and 3V. It is more than 1LSB when it comes to bigger voltage. Actually there is no certain quantitative value to describe this. Other parameters result such as full scale range is 4.68V, offset error is 0.010V and gain error is 93.6%. This measurement can be performed by applying an appropriate data input. The value can be shown quantitatively. From measurement, we conclude that this DAC is a very high resolution and accuracy. The project shows a good result and succeeds to achieve its objective.